Role of Antioxidants in Prevention of Cardio-Vascular Diseases - zahra majde teimoori (Guilan University of Medical Sciences, 2006)
Coronary heart diseases are the most preventable non-contagious diseases, but unfortunately, ‎it is one of the major causes of mortality among humans in the industrialized and semi-‎industrialized countries. It is predicted that if this trend continues, it will lead to the death of ‎approximately over ‎‏25‏‎ million people in the world by ‎‏2020‏‎. On the other hand, according to ‎investigations it has been proven that antioxidants are substances that can contribute to the ‎risk reduction of cardio-vascular diseases (CVD). ‎ This article has introduced the role of antioxidants in decreasing the risk of CVD. ‎Experimental studies have shown that the most common factor related to the incidence of ‎CVD is arteriosclerosis. In this connection, free radicals of oxidant substances obtained from ‎the metabolism of high density cholesterols always play an essential and significant role. Other ‎studies also demonstrate the contradictory role of antioxidants in the struggle against these ‎detrimental substances and thus its role in delaying the process of atherosclerosis.‎ Considering the importance of nutrition in the occurrence of most diseases, on one hand, and ‎the establishment of essential role of antioxidants in the prevention of the common diseases ‎such as CVDs, on the other hand, it is suggested that the education and encouragement of the ‎general public for consumption of foodstuffs rich in these substances as well as the greater ‎and optimal use of antioxidants and food supplements containing these substances in the food ‎industries of our country is suggested. ‎